The problem of removal vibrations in the formation of micro- and nano-roughness on friction effective surfaces for increasing accuracy processing - Горенко, М.В. (Problems of Tribology, 2014)
In the work considers the problem of eliminating vibrations in the formation of micro-and nano-roughness of friction effective surfaces to improve the accuracy of processing, influence of kinematic scheme for vibratory processes and first time proposed the way of solve problems by using interactive correction methods of speed distribution on the trajectory of the tool, that processes, taking into account the structural features of the automated processe mechanism on the example of the use of curvilinear movement trajectory, wich formed by the second and higher orders segments.